Idea powrotu Ormian z rozproszenia do narodowej ojczyzny w świetle memoriałów Roberta Bogdanowicza z 1877 i 1884 roku (Lehahayer, 2020)
The idea of the return of Armenians from dispersal to their historicalhomeland in the context of the Robert Bogdanowicz’s memorials from 1877 and 1884The article contains an analysis of the two memorials, of which the first,from 1877, remained in the manuscript, and the second, from 1885, was publishedunder the title The question of the Church of Armenian rite and its mission, as wellas the Armenian question in the East in their own country. Both were compiled byRobert Bogdanowicz, a landowner, a descendant of an Armenian family who hadlived in Poland for at least four centuries. The memorials were inspired by the author’scorrespondence with the Minister of Internal Affairs of the Russian Empire,Mikhail Loris-Melikov, and Armenian archbishop Gabriel Ayvazovski. Bogdanowiczdiscussed the issue of Armenia’s independence, and in Russia he saw a patronof the struggle for national liberation. He called for the return of Polish Armeniansto their homeland in order to rebuild the state and its culture and spread ArmenianCatholicism there. Bogdanowicz can be considered one of those political thinkers ofmodern Armenia who were the co-founders of the ideology of Armenian nationalism,although the language barrier excluded its influence on other parts of the Armeniandiaspora. He did not receive any significant response among his peers atfirst, but then gained a few like-minded followers in the generations that followed.Therefore, he can be considered a protagonist of the Armenian national renaissanceof Polish Armenians that took place between the two world wars, and whose furtherdevelopment was blocked by the destruction of their homeland in former Galicia andtheir dispersion after 1944.